Macroeconomic Determinants of Air Cargo Flows in Ghana - Adenigbo, Adedotun Joseph; Mageto, Joash; Luke, Rose (Latin American Journal of Trade Policy, 2022)
Air cargo flows in a country represent air trade volume involving the exchange of goods between countries, and it is significant to the economic development of nations. However, the instability of macroeconomic variables makes air cargo trade fluctuate with its decision-making challenges. This paper examines air cargo flows by volume, origin, destination, and Ghana’s macroeconomic determinants of air trade. The study collected categorized cargo volume data from Ghana Airport Company Ltd and macroeconomic data from the Bank of Ghana from 1991 to 2020. The study employed descriptive, correlation and regression to analyze data. ArcGIS mapping shows that European countries form the primary origins and destinations of cargo traffic in Ghana. The regression analysis found exchange rate (r = 0.43) and interest rate (r = 0.50) as the significant macroeconomic variables influencing air cargo trade in Ghana. This study highlights the need for policy decisions that promote an extensive bilateral exchange and lower interest rates for local production and export goods by air in Ghana.